Minerals in esophageal samples from steers on native bluestem pastures - Harbers, L.H.; Unoh, J.E.; Sapienza, D.A.; Brent, B.E.; Peischel, H.A.; Whitney, J.D.; Smith, E.F. (Kansas State University. Agricultural Experiment Station, 2011)
This report summarizes monthly mineral contents of burned and control native bluestem pastures determined with samples from fisulated steers. Burning decreases calcium (Ca), potassium (K), and iron (Fe), and slightly decreases zinc (Zn). All minerals we studied were adequate for grazing cattle except that magnesium (Mg) and Potassium (K) appear to be borderline during winter months.
Keywords: Beef; Steers; Bluestem pasture; Minerals